Perspectives of Students with Special Needs on Social Interaction of Regular Students in Padang City - Putri, Sentia Andani; Efendi, Rizka Fadhillah; Purwanti , Indah Mugianti; Mulyadi, Mulyadi; Damri, Damri; Iswari, Mega; Murni, Irda; Rahmahtrisilvia, Rahmahtrisilvia; Tsaputra, Antoni (Angstrom Centre of Education, 2024)
This research aims to explain the perspective of students with special needs regarding social interactions with regular students in Padang City from elementary to high school/vocational school levels. This research uses a qualitative descriptive approach with a case study plan. Data was collected through questionnaires given to students with special needs plus interviews and observations used to determine the perspective of students with special needs regarding social interactions carried out by regular students. Data processing techniques that use statistical categorization which is divided into three categories: high, medium and low. The research results show that students with special needs have various perspectives on their social interactions with regular students. Some students with special needs feel accepted and appreciated by regular students, while others feel ignored or even bullied. Therefore in the data there are high, medium and low categories depending on how the interactions are found.